2019
DOI: 10.1093/gastro/goy046
|View full text |Cite
|
Sign up to set email alerts
|

Management of complicated gallstones in the elderly: comparing surgical and non-surgical treatment options

Abstract: Objective The aim of this study was to evaluate the differences in clinical outcomes of endoscopic retrograde cholangiopancreatography (ERCP), ERCP followed by cholecystectomy (EC) and percutaneous aspiration (PA) in the elderly population with choledocholithiasis. Methods We included a total of 43 338 elderly patients aged 60 years or older and 45 295 patients younger than 60 years for comparison in our study. Data were obtained from the Nationwide Inpatient Sample (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
18
0
2
Order By: Relevance
“…In the present study, age was not the risk factor of PEP. However, in the comparison between elderly patients aged 60 years or older and younger than 60 years, younger than 60 years group was significantly a larger pancreatic volume . Thus, younger age may increase the incidence of PEP.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, age was not the risk factor of PEP. However, in the comparison between elderly patients aged 60 years or older and younger than 60 years, younger than 60 years group was significantly a larger pancreatic volume . Thus, younger age may increase the incidence of PEP.…”
Section: Discussionmentioning
confidence: 81%
“…According to the guideline forwarded by Pisano, laparoscopic cholecystectomy should be considered for all; the age, on its own, is not a contraindication for surgery (Pisano et al 2019). While Nassar in his study found that age of the patient is a significant factor determining the likelihood of death and the length of hospital stay after any type of procedure of gallstones removal (Nassar & Richter 2019). Laparoscopic and open cholecystectomy were used for our patients in this study, with a conversion from laparoscopic to open procedure at a rate of 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with a history of cholecystectomy, ERCP is the preferred method for removing bile duct stones. A retrospective study comparing 43,338 older patients (60 years) with 45,295 younger patients (<60 years) from the Nationwide Inpatient Sample database suggested that ERCP followed by cholecystectomy was characterized by lowest mortality among the older patients and should be the preferred method of management for patients with complicated gallstone disease, regardless of the age (Nassar and Richter 2019). However, in this study, although mortality was found to be significantly higher in ERCP compared to ERCP followed by cholecystectomy in patients 60-79 years old, death rates were noted to be comparable between the two groups in patients more than 80 years old.…”
Section: Risk Stratification and Managementmentioning
confidence: 99%